The supportive care needs and its influencing factors among thyroid cancer patients after surgery: A cross-sectional study - Cai, Ming; Gou, Juxiang (Frontiers in Surgery, 2023)
Objective To study the supportive care needs (SCNS) of thyroid cancer (TC) patients after surgery, and to identity its influencing factors. Methods By convenience sampling method, total of 115 patients undergoing thyroid surgery who met the inclusion criteria from May 2021 to July 2021 were selected as the research objects. The general information questionnaire, Supportive Care Need Survey Short-Form (SCNS-SF34), functional subscale of European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) were used to investigate these patients. Results The average score for the items of SCNS-SF34 in 102 TC patients was 2.15 ± 0.71. The domain with the highest item average score was “health system information needs” (2.48 ± 1.17). The domain with the highest unsatisfied rate was “psychological needs” (69.6%). The item with the highest average score was “fear of cancer spreading” in the psychological needs domain (2.80 ± 1.48). The scores of physical function (r = −0.431, P < 0.001), role function (r = −0.428, P < 0.001), cognitive function (r = −0.531, P < 0.001), emotional function (r = −0.388, P < 0.001), social function (r = −0.464, P < 0.001) were correlated with the total score of SCNS-SF34. The univariate analysis of SCNS-SF34 scores showed that TC patients who were women (t = 2.013, P = 0.047), older (F = 1.353, P = 0.013), and with longer hospital stays (F = 3.705, P = 0.028) had higher demand of SCNS. The results of multiple linear regression analysis showed that the significant variables that entered the regression equation were gender, age, length of stay in hospital, cognitive function and social function (P < 0.05). Conclusion TC patients after surgery have many SCNS in different domains. It is necessary to focus on women, older patients, patients with long hospital stays and poor functioning. The implementation of a supportive care screening tool is recommended and the individualized interventions need to be developed to provide targeted support and care.